الوسائل التعليمية المستخدمة في منهج تعليم اللغة العربية للمجلس الوطني بكليات التربية بنيجيريا : دراسة تقويمية - أبيؤدن، مصطفى طيب (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2022)
This study aims to determine the effectiveness of the instructional materials in the Arabic language teaching curriculum for the National Council of Colleges of Education in Nigeria. The researcher in this study relied on the descriptive approach to achieve these goals by reviewing printed scientific documents and documents. In addition to using research, books, scientific journals and websites, and the analytical method by distributing questionnaires to lecturers and students, this is to know their opinions about their readiness to use educational aids. Modern. The study sample consisted of 182 male and female students and 10 Arabic language lecturers. A three-section student questionnaire was developed for data collection. The first section contained demographics, and the second section had questions about the availability of educational aids in the faculties of education. The last section was about the extent of educational aids used in the faculties of education. A questionnaire was developed for the lecturers about their readiness for modern teaching aids. At the end of the analysis, this research reached several results. The most important of these is that modern educational means are not available in the Arabic language teaching curriculum for the National Council. It needs rapid development to improve Arabic language students in the college. The results confirmed a positive impact on receiving students towards using the means of Instruction to teach the Arabic language. The lecturers agreed on that.